Applying Innovation Method to Assess English Speaking Performance on Communication Apprehension - Wang, Li-Jyu; Chang, Hung-Fan (BELT - Brazilian English Language Teaching Journal, 2011)
A growing number of research studies are now available to shed some light on ELT methods. Currently, educational portfolios are implemented in Science, Mathematics and Geography and also have become widely used in ELT. When the students prepared their own portfolios, they self-monitored their performances. The purpose of this study was to investigate the effects of self-monitoring and portfolios on college students’ English speaking performance. The participants involved in this study were 60 college students majoring in the Department of Applied Foreign Languages at one university of technology in Taiwan. In the study, descriptive statistics and t-tests were used to test the effects of using communication apprehension. In the portfolio group, the students’ communication apprehension was lowered. In conducting this study, the researcher hoped that this research could provide valuable perspective on the use of portfolios and self-monitoring.